Monolayer CS as a metal-free photocatalyst with high carrier mobility and tunable band structure: a first-principles study. (17th January 2018) - Yang, Xiao-Le; Ye, Xiao-Juan; Liu, Chun-Sheng; Yan, Xiao-Hong
Abstract: Producing hydrogen fuel using suitable photocatalysts from water splitting is a feasible method to harvest solar energy. A desired photocatalyst is expected to have suitable band gap, moderate band edge position, and high carrier mobility. By employing first-principles calculations, we explore a α -CS monolayer as a metal-free efficient photocatalyst. The α -CS monolayer shows good energetic, dynamic, and thermal stabilities and is insoluble in water, suggesting its experimental practicability. Monolayer and bilayer α -CS present not only appropriate band gaps for visible and ultraviolet light absorption but also moderate band alignments with water redox potentials in pH neutral water. Remarkably, the α -CS monolayer exhibits high (up to 8453.19 cm 2 V −1 s −1 for hole) and anisotropic carrier mobility, which is favorable to the migration and separation of photogenerated carriers. In addition, monolayer α -CS experiences an interesting semiconductor-metal transition by applying uniaxial strain and external electric field. Moreover, α -CS under certain strain and electric field is still dynamically stable with the absence of imaginary frequencies. Furthermore, we demonstrate that the graphite (0 0 1) surface is a potential substrate for the α -CS growth with the intrinsic properties of α -CS maintaining. Therefore, our results could pave the way for the application of α -CS as a promising photocatalyst.